Optimalisasi Tugas dan Fungsi Camat dalam Pelayanan Publik Kecamatan Siritaun Wida Timur Kabupaten Seram Bagian Timur - Rumain, Sahidin; Tuanaya, Wahab; Kotaromalos, Amir Faisal (Prodi Ilmu Pemerintahan, Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Pattimura, 2023)
The purpose of this study is to describe the optimization of the duties and functions of the sub-district head in public services in District of Siritaun Widatimur. This study uses qualitative research methods through observation, interviews and documentation. The data was obtained at the Siritaun Widatimur sub-district office through the sub-district head, sub-district secretary, officials, five community leaders and five youth leaders. This study aims to determine the duties and functions of the sub-district head in providing services to the community in the Siritaun Widatimur sub-district. The results of this study indicate that the functions and duties of the sub-district head in providing public services are considered good, although there are some individuals or individuals who are not professional in doing their work.